High order concentrated matrix-exponential distributions. Issue 2 (2nd April 2020) - Horváth, Gábor; Horváth, Illés; Telek, Miklós
Abstract: This paper presents matrix-exponential (ME) distributions, whose squared coefficient of variation (SCV) is very low. Currently, there is no symbolic construction available to obtain the most concentrated ME distributions, and the numerical optimization-based approaches to construct them have many pitfalls. We present a numerical optimization-based procedure which avoids numerical issues.